Black Raspberries and Their Anthocyanin and Fiber Fractions Alter the Composition and Diversity of Gut Microbiota in F-344 Rats. (18th August 2017) - Pan, Pan; Lam, Vy; Salzman, Nita; Huang, Yi-Wen; Yu, Jianhua; Zhang, Jianying; Wang, Li-Shu
ABSTRACT: Natural compounds can alter the diversity and composition of the gut microbiome, potentially benefiting our health. We previously demonstrated chemopreventive effects of black raspberries (BRBs) in colorectal cancer, which is associated with gut dysbiosis. To investigate the effects of whole BRBs and their fractions on gut microbiota, we fed F-344 rats a control diet, 5% BRBs, the BRB anthocyanin fraction, or the BRB residue fraction for 6 weeks. Feces were collected at baseline and at weeks 3 and 6, and bacterial sequence counts were analyzed. We observed distinct patterns of microbiota from different diet groups. Beta diversity analysis suggested that all diet groups exerted time-dependent changes in the bacterial diversity. Hierarchical clustering analysis revealed that post-diet fecal microbiota was segregated from baseline fecal microbiota within each diet. It is interesting to note that fractions of BRBs induced different changes in gut bacteria compared to whole BRBs. The abundance of specific microbial species known to have anti-inflammatory effects, such as Akkermansia and Desulfovibrio, was increased by whole BRBs and their residue. Further, butyrate-producing bacteria, e.g., Anaerostipes, were increased by whole BRBs. Our results suggest that whole BRBs and their fractions alter the gut microbiota in ways that could significantly influence human health.